2021
DOI: 10.14202/vetworld.2021.2809-2816
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Clostridium perfringens in small-scale commercial broiler flocks in Mymensingh district of Bangladesh

Abstract: Background and Aim: Necrotic enteritis (NE) is one of the most prevalent diseases in broiler poultry caused by Clostridium perfringens connected with significant economic losses. A cross-sectional survey was conducted in Mymensingh district of Bangladesh to assess the prevalence of C. perfringens through toxinotyping molecular assay and confirm the risk factors for NE, including antimicrobial-resistant (AMR) status of the isolates. Materials and Methods: We included 40 small-scale commercial broiler farms ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…These study findings could not compare explicitly in country context due to the lack of substantial reference data on the prevalence rate of NE layer chicken in Bangladesh. However, a recent study confirmed a flock level prevalence of C. perfringens as 10.3% in broiler chicken (Tresha et al, 2021). Additionally, a few past studies established the incidence rate of C. perfringens that varies from 0.4 to 1% based on clinical findings and post mortem lesions (Hossain et al, 2012;Islam et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…These study findings could not compare explicitly in country context due to the lack of substantial reference data on the prevalence rate of NE layer chicken in Bangladesh. However, a recent study confirmed a flock level prevalence of C. perfringens as 10.3% in broiler chicken (Tresha et al, 2021). Additionally, a few past studies established the incidence rate of C. perfringens that varies from 0.4 to 1% based on clinical findings and post mortem lesions (Hossain et al, 2012;Islam et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Total genomic DNA was extracted from pure colonies of the bacteria using the Total DNA Extraction Kit as described by Tresha et al (2021). The size (236 bp of the beta toxin of C. perfringens) of the target gene (CPB gene) was amplified and the Polymerase Chain Reaction (PCR) was carried out in a Thermal Cycler (2720 Thermal Cycler; Applied Biosystem).…”
Section: Molecular Testmentioning
confidence: 99%
“…The improper antimicrobial drug used for humans is diffusive in developing countries and is a significant contributor to growing the public health threat of AMR-resistant bacteria (Roess et al, 2013). In recent years, the indiscriminate use of antibiotics in animals and poultry is thought to be an important factor to develop of AMR Al-Salauddin et al, 2015;Sohidullah et al, 2016;Rahman et al, 2016;Talukder and Ahmed, 2016;Roy et al, 2017;Jahan et al, 2017;Kabir et al, 2018a;Kabir et al, 2018b;Kamal et al, 2018;Alam et al, 2019;Rumi et al, 2019;Saif et al, 2019;Masud et al, 2020;Alam et al, 2020;Sarker et al, 2020;Mridha et al, 2020;Matubber et al, 2021;Uddin et al, 2021;Tresha et al, 2021;Eashmen et al, 2021;Haque et al, 2021;Hosain et al, 2021;Arif et al, 2022;Hoque et al, 2022). In Bangladesh, the most common reason for choosing an antimicrobial is personal experience and perception (68%), rather than the cultural sensitivity test which may be due to a lack of vet diagnostic facilities and the unwillingness of the veterinary personnel (Pokharel et al, 2020).…”
Section: Development Of Antimicrobial Resistance (Amr)mentioning
confidence: 99%